Perancangan Strategi Digital Campaign UMKM Kuliner Sate Maranggi Hj. Yetty - Iskandar, Moniqca Sandha; Voutama, Apriade (KOMPUTEK, 2025)
Abstract. This study aims to design a digital campaign strategy for culinary MSMEs, with a case study on Sate Maranggi Hj. Yetty. In the digital era, marketing through social media and paid advertising plays a crucial role in increasing brand awareness, engagement, and sales conversion. This research employs a qualitataive approach through competitor analysis, literature review, and social media observation. The results indicate that the designed campaign strategy consists of four main pillars: inspirational, educational, entertaining, and convincing content. Additionally, the optimization of Meta Ads and Tiktok Ads is utilized to expand market reach. This strategy aims to increase social media engagement by 30%, gain 15,000 new followers, boost restaurant visits by 20%, and raise sales by 20% within six months. The primary challenges identified include the limited use of paid advertising and minimal promotional strategies. Further development can be carried out through direct campaign implementation and the optimization of customer retention strategies via digital loyalty programs. With a structured digital marketing strategy, culinary MSMEs can enhance their competitiveness in the increasing.